PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN KUD KARYA BHAKTI NGANCAR KEDIRI - Allail Niken Suciani; Edy Suwasono; Zaenul Muttaqien (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This study has a limitation on the aspect of human resource management to determine the effect of Compensation and Career Development on Job Satisfaction of KUD Karya Bhakti Ngancar Kediri employees. By using a sample of 33 respondents and using purposive sampling technique, the research method used was observation, interviews, documentation, questionnaires and literature study. As well as data analysis techniques in this study using statistical tests through validity and reliability tests, classical assumption tests, multiple linear regression tests, t-test hypotheses and f-tests using SPSS. Based on the results of the analysis, it was found that the variable influence of compensation and career development had a simultaneous effect on employee job satisfaction, with a value of Sig. 0.000 <0.05. Partially, compensation had a significant effect on employee job satisfaction, with a value of Sig. 0.003 <0.05 and career development has a significant effect on employee job satisfaction, with a value of Sig. 0.013 < 0.05. The regression equation: Y = 0.827 + 0.628X1 + 0.529X2 and the coefficient of determination is 55.3%.